2015
DOI: 10.1080/08870446.2015.1007982
|View full text |Cite
|
Sign up to set email alerts
|

Perseverative thoughts and subjective health complaints in adolescence: Mediating effects of perceived stress and negative affects

Abstract: Stable tendency to perseverative thoughts such as trait rumination and worry can influence somatic health. The purpose of the study was to investigate the relationship between perseverative thoughts and somatic complaints, and the possible mediating effects of perceived stress, negative and positive affectivity in adolescence. Having an acute or a chronic condition was also assessed to be controlled for and to reveal their effects on symptom reporting. Three hundred and six adolescents from 7th to 12th grade w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 100 publications
3
7
0
2
Order By: Relevance
“…More specifically, both regression and fsQCA analyses show that girls tend to present more emotional symptoms than boys. These findings are in line with previous studies, which indicated that girls may have more persistent thoughts or worries and therefore internalise more emotional symptoms [45]. In behavioural problems, sex seems to have some influence, but to a lesser extent than emotional symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…More specifically, both regression and fsQCA analyses show that girls tend to present more emotional symptoms than boys. These findings are in line with previous studies, which indicated that girls may have more persistent thoughts or worries and therefore internalise more emotional symptoms [45]. In behavioural problems, sex seems to have some influence, but to a lesser extent than emotional symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to these socio-emotional protective factors, there are also personal characteristics that may affect adolescent adjustment and well-being, such as sex and age. As regards psychological adjustment, boys present more behavioural problems [44]; whereas girls tend to experience more emotional symptoms [45]. In terms of age, young people before puberty (pre-adolescents) adjust more easily to internal and external changes than adolescents [46,47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Con todo ello, estos resultados refuerzan estudios anteriores que informan que los jóvenes con alta autoestima muestran mayor adaptación a eventos vitales estresantes (Kocayörük y Şimşek, 2016;Thompson et al, 2016); aquellos con baja autoestima presentan mayor riesgo en su salud mental y bienestar emocional (von Soest, Wichstrøm y Kvalem, 2016), siendo determinante del desajuste psicológico en los adolescentes (Keane y Loades, 2016;Reina y Oliva, 2015;Schoeps et al, 2019). La valoración que cada uno hace de sí mismo, junto con las habilidades de percepción, comprensión y regulación emocional reduce los síntomas emocionales y las conductas disfuncionales, ayudando en la adaptación a nivel físico y psicológica de la adolescencia (Bleidorn et al, 2016;Carlo et al, 2014;Kökönyei et al, 2015).…”
Section: Discusión Y Conclusionesunclassified
“…Es esencial ante los problemas y desafíos que las personas enfrentan en la vida, y desempeña un rol importante en el afrontamiento de situaciones estresantes, actuando como un almacén de sentimientos positivos (Rosenberg y Owens, 2001). Se han evidenciado los beneficios del desarrollo de las habilidades emocionales y de la autoestima en la prevención del desajuste psicológico de los adolescentes (Bleidorn et al, 2016;Carlo et al, 2014;Kökönyei et al, 2015;Reina y Oliva, 2015;Schoeps, Tamarit, González y Montoya-Castilla, 2019), identificándola como variable mediadora y explicativa del impacto de variables socioemocionales en dicho ajuste, lo que justifica su inclusión en estudios presentes y futuros (Kocayörük y Simsek, 2016;Thompson, Wojciak y Cooley, 2016).…”
Section: Introductionunclassified